Atomic solution structure of Mycobacterium abscessus F-ATP synthase subunit ε and identification of Ep1MabF1 as a targeted inhibitor - Shin, Joon (2022)
Mycobacterium abscessus (Mab) is a nontuberculous mycobacterium of increasing clinical relevance. The rapidly growing opportunistic pathogen is intrinsically multi-drug-resistant and causes difficult-to-cure lung disease. Adenosine triphosphate, generated by the essential F1 FO ATP synthase, is the major energy currency of the pathogen, bringing this enzyme complex into focus for the discovery of novel antimycobacterial compounds. Coupling of proton translocation through the membrane-embedded FO sector and ATP formation in the F1 headpiece of the bipartite F1 FO ATP synthase occurs via the central stalk subunits γ and ε. Here, we used solution NMR spectroscopy to resolve the first atomic structure of the Mab subunit ε (Mabε), showing that it consists of an N-terminal β-barrel domain (NTD) and a helix-loop-helix motif in its C-terminal domain (CTD). NMR relaxation measurements of Mabε shed light on dynamic epitopes and amino acids relevant for coupling processes within the protein. We describe structural differences between other mycobacterial ε subunits and Mabε's lack of ATP binding. Based on the structural insights, we conducted an in silico inhibitor screen. One hit, Ep1MabF1, was shown to inhibit the growth of Mab and bacterial ATP synthesis. NMR titration experiments and docking studies described the binding epitopes of Ep1MabF1 on Mabε. Together, our data demonstrate the potential to develop inhibitors targeting the ε subunit of Mab F1 FO ATP synthase to interrupt the coupling process.